Hubungan Kepuasan Kerja Terhadap Keterikatan Kerja pada Sat Samapta Polresta X - Ni Made Sintya Noviana Utami; Luh Putu Ratih Andhini; Si Luh Nyoman Trisna Ulandari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The police are a law enforcement institution with fundamental duties and obligations This study aims to analyze the relationship between job satisfaction and job engagement, as well as describe the condition of job satisfaction and engagement in Sat Samapta Polresta X. In addition, this study wants to identify the contribution of job satisfaction to job engagement in the institution. In addition, this study wants to identify the contribution of job satisfaction to work engagement in the institution Using a quantitative approach and an online questionnaire, this study involved 70 members of Sat Samapta Polresta X as respondents. The instruments used consisted of a job attachment scale with 21 items that had validity ranging from 0.288 to 0.769 and reliability of 0.877, and a job satisfaction scale with 29 items whose validity ranged from 0.251 to 0.644 and reliability of 0.914, which were adapted from Elvani's (2019) research referring to Luthans' theory. The results revealed a significant relationship between job satisfaction and job attachment in Sat Samapta Polresta X, with a significance value of 0.000 (α < 0.05) and an R Square value of 0.703. This indicates that job satisfaction contributes 70.3% to work engagement. The positive correlation R value of 0.838 indicates that increasing job satisfaction has the potential to improve job attachment of Sat Samapta Polresta X members, and can improve their work performance and motivation. This study concludes that job satisfaction contributes significantly to work engagement at Sat Samapta Polresta X, with high job satisfaction playing an important role in increasing work engagement. The researcher suggests to be broader and explore factors in work engagement such as: leadership, communication, health, and security.